The Effect of Rational Emotive Behavior Therapy (REBT) Intervention on Reducing Anxiety and Improving the Quality of Self-Coping of Pregnant Women in the Working Area of the Nilam Sari Community Health Center, Bukittinggi City 2015 - Fitri, Sari Rahma (Kirana Publisher (KNPub), 2024)
One indicator of the success of health services is reflected in the decline in maternal mortality. but in reality in Indonesia it is still relatively high. One of the factors that affect the health of pregnant women is excessive anxiety. The result of various studies in the world show, excessive anxiety in pregnancy adversely affect the quality of pregnancy and can lead to complications, mental health development of children. This study aims, know the effect of interventions Rational Emotive Behavior Therapy (REBT) to decrease anxiety and quality of coping pregnant women in the region Puskesmas Nilam Sari Bukittinggi 2015. The method used in this study is Quasy Experiment design non randomized pretest – post test without control with a sample of 16 pregnant women categories moderate to very hight anxiety. Measuring Instruments used quesionnaires Pregnancy Anxiety Scale (PSA), Pregnancy Related Anxiety Scale (PRAS), Revised Ways Of Coping Scale (WCQR), and an Intervention Module designed practicing with psychologist regarding principle of step Rational Emotive Behavior Therapy (REBT). Analysis of data using Friedman test, Wilcoxon and Marginal Homogeneity test.